A new genus of cave-dwelling springtails (Collembola, Neanuridae), from Serbia - Lučić Luka R.; Stanković Snežana V. (Archives of Biological Sciences, 2002)
A new genus and a new species from the collembolan family Neanuridae Trojanura mirocensis n. g., n. sp. has been described from the Buronov Ponor, village Miroč, Miroč Mt. (The Iron Gate), East Serbia, Yugoslavia. This form represents a very old remnant of the once existing tropical and subtropical fauna. It is also an endemic form, restricted only to cave habitats pertaining to the area studied.